OsDDM1b Controls Grain Size by Influencing Cell Cycling and Regulating Homeostasis and Signaling of Brassinosteroid in Rice - Guo, Mingliang; Zhang, Wenchao; Mohammadi, Mohammad Aqa; He, Zhimei; She, Zeyuan; Yan, Maokai; Shi, Chao; Lin, Lingwei; Wang, Aqiong; Liu, Jindian; Tian, Dagang; Zhao, Heming; et al. (Frontiers in Plant Science, 2022)
Snf2 family proteins are the crucial subunits of chromatin-remodeling complexes (CRCs), which contributes to the biological processes of transcription, replication, and DNA repair using ATP as energy. Some CRC subunits have been confirmed to be the critical regulators in various aspects of plant growth and development and in epigenetic mechanisms such as histone modification, DNA methylation, and histone variants. However, the functions of Snf2 family genes in rice were poorly investigated. In this study, the relative expression profile of 40 members of Snf2 family in rice was studied at certain developmental stages of seed. Our results revealed that OsCHR741/OsDDM1b (Decrease in DNA methylation 1) was accumulated highly in the early developmental stage of seeds. We further analyzed the OsDDM1b T-DNA insertion loss-of-function of mutant, which exhibited dwarfism, smaller organ size, and shorter and wider grain size than the wild type (Hwayoung, HY), yet no difference in 1,000-grain weight. Consistent with the grain size, the outer parenchyma cell layers of lemma in osddm1b developed more cells with decreased size. OsDDM1b encoded a nucleus, membrane-localized protein and was distributed predominately in young spikelets and seeds, asserting its role in grain size. Meanwhile, the osddm1b was less sensitive to brassinosteroids (BRs) while the endogenous BR levels increased. We detected changes in the expression levels of the BR signaling pathway and feedback-inhibited genes with and without exogenous BR application, and the alterations of expression were also observed in grain size-related genes in the osddm1b. Altogether, our results suggest that OsDDM1b plays a crucial role in grain size via influencing cell proliferation and regulating BR signaling and homeostasis.